Analysis of Amtsāl al-Kāminah in Surah al-Wāqi‘ah: A Stylistic Study - Lintang Luthfi Kirani; Faiza Kamila; Afif Naufal Andrean Yudistira; Thariqatul Amalia; Syaima Salsabila Ahmad; Jauhar Hatta (ZAD Al-Mufassirin, 2025)
The Qur’an contains verses of amtsal (parables) that can be used as reminders for Muslims. Amtsal can serve as an effective alternative reminder for the Muslim community, as the language used in the Qur’an is very beautiful, minimizing the risk of offending people. The purpose of this study is to analyze the verses found in Surah Al-Waqi'ah that use amtsal kaminah. This research uses a library method with sources from the Qur’an along with its translation and interpretation, as well as other relevant sources. The study reviews the verses in the Qur’an that contain amtsal kaminah. The findings of this research show that amtsal kaminah are present in Surah Al-Waqi’ah. One amtsal kaminah conveys the idea that "the best measure of a matter is the moderate one," which is found in three verses: 3, 7, and 13. Another amtsal kaminah suggests that "the news being conveyed does not reflect the real situation," which is found in nine verses: 12, 15, 17, 19, 22, 23, 25, 28, and 33. The final amtsal kaminah pertains to "someone who commits an unjust act will certainly face retribution," which is found in seven verses: 42, 43, 44, 52, 54, 93, and 94. In total, the researcher identified 15 verses containing amtsal kaminah in Surah Al-Waqi’ah.